Evolution of cellular immunotherapy: from allogeneic transplant to dendritic cell vaccination as treatment for multiple myeloma. (October 2012) - Arnason, Jon; Avigan, David
The promise of cellular therapy as treatment for multiple myeloma is highlighted by the observation that allogeneic transplantation results in durable remissions in a subset of patients. The potency of the graft-versus-myeloma effect is supported by the decreased risk of relapse seen in patients with graft-versus-host disease and disease response following donor lymphocyte infusions. However, the lack of specificity of the alloreactive lymphocytes limits their therapeutic efficacy and results in significant treatment-related morbidity and mortality. A major area of investigation is the development of cancer vaccines to generate myeloma-specific immunity that selectively targets malignant cells while minimizing toxicity to normal tissues. Critical elements required to develop an effective vaccine strategy involve the identification of myeloma-associated antigens, enhancement of antigen presentation, and reversing the immunosuppressive milieu induced by the disease. Dendritic cells are potent APCs that represent an ideal platform for vaccination. Strategies for vaccine design include the loading of individual antigens as well as the use of whole tumor cells as a source of myeloma antigens. Vaccination has been examined in the postautologous transplant setting in which disease cytoreduction and depletion of Tregs is associated with enhanced vaccine response. Recent efforts have also included exploration of immune modulatory agents that target inhibitory pathways to enhance vaccine response and create a more durable antitumor immunity.